Modulation of Solvation Structure and Electrode Work Function by an Ultrathin Layer of Polymer of Intrinsic Microporosity in Zinc Ion Batteries. Issue 25 (2nd May 2022) - Heo, Jiyun; Hwang, Young‐Eun; Doo, Gisu; Jung, Jinkwan; Shin, Kyungjae; Koh, Dong‐Yeun; Kim, Hee‐Tak
Abstract: Zinc ion batteries are promising candidates for large‐scale energy storage systems. However, they suffer from the critical problems of insufficient cycling stability due to internal short‐circuiting by zinc dendrites and zinc metal orphaning. In this work, a polymer of intrinsic microporosity (PIM‐1) is reported as an ion regulating layer and an interface modulator, which promotes a uniform Zn plating and stripping process. According to spectroscopic analyses and computational calculations, PIM‐1 enhances the reaction kinetics of a Zn metal electrode by altering the solvation structure of Zn 2+ ions and increasing the work function of the Zn surface. As a result, the PIM‐1 coating significantly improves the cyclability (1700 h at 0.5 mA cm −2 ) and Coulombic efficiency (99.6% at 3 mA cm −2 ) of the Zn/Zn 2+ redox reaction. Moreover, the PIM‐1 coated Zn operates for more than 200 h at 70% Zn utilization even under 10 mA cm −2 and 110 h at 95% Zn utilization of the Zn metal electrode. A Zn||V2 O5 full cell employing the PIM‐1 layer exhibits seven times longer cycle life compared to the cell using bare Zn. The findings in this report demonstrate the potential of microporous materials as a key ingredient in the design of reversible Zn electrodes. Abstract : Polymer of intrinsic microporosity (PIM‐1) is served as an ion regulating layer and an interface modulator which can change the solvation structure of Zn 2+ ion and work function of Zn metal. As a result, PIM‐1 enhances the reaction kinetics of Zn redox reaction and promotes a uniform Zn deposition/dissolution process.